2017
DOI: 10.1371/journal.pone.0189000
|View full text |Cite
|
Sign up to set email alerts
|

Expression of phosphatase of regenerating liver (PRL)-3, is independently associated with biochemical failure, clinical failure and death in prostate cancer

Abstract: BackgroundProstate cancer (PC) stratification needs new prognostic tools to reduce overtreatment. Phosphatase of regenerating liver (PRL-3) is a phosphatase found at high levels in several cancer types, where its expression is associated with survival. A recent PC cell line study has shown it to be involved in PC growth and migration.MethodsWe used a monoclonal antibody to evaluate the expression of PRL-3 in PC tissue of patients in an unselected cohort of 535 prostatectomy patients. We analyzed associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Similar to the cancers described above, upregulated PRL‐3 in tumors has been found in cervix , kidney , glioma , bladder , melanoma , lung , and prostate cancers. As for PRL‐1 and ‐2, using microarray analysis, mRNA levels were shown to be upregulated in pancreatic tumor samples compared with those of normal pancreas .…”
Section: Prl Expression In Tumors and Metastases: Emerging Biomarker supporting
confidence: 70%
See 1 more Smart Citation
“…Similar to the cancers described above, upregulated PRL‐3 in tumors has been found in cervix , kidney , glioma , bladder , melanoma , lung , and prostate cancers. As for PRL‐1 and ‐2, using microarray analysis, mRNA levels were shown to be upregulated in pancreatic tumor samples compared with those of normal pancreas .…”
Section: Prl Expression In Tumors and Metastases: Emerging Biomarker supporting
confidence: 70%
“…However, one study indicated that PRL-3 expression has no clinical role in ovarian carcinoma, whereas surprisingly PRL-1 and PRL-2 expression is associated with longer survival [113]. Similar to the cancers described above, upregulated PRL-3 in tumors has been found in cervix [114], kidney [115,116], glioma [117,118], bladder [119], melanoma [120], lung [121], and prostate [122][123][124] cancers. As for PRL-1 and -2, using microarray analysis, mRNA levels were shown to be upregulated in pancreatic tumor samples compared with those of normal pancreas [125].…”
Section: Prl Expression In Tumors and Metastases: Emerging Biomarker mentioning
confidence: 85%
“…7 Various studies have reported upregulation of PRL3 in CRC. [9][10][11] PRL3 has also been found to be overexpressed in many other human cancer types such as prostate cancer, 12,13 gastric cancer, 14,15 ovarian cancer, 16 and chronic myeloid leukemia. 17 PRL3 promotes cell survival and epithelial to mesenchymal transition (EMT) by acting upstream of phosphatidylinositol-3 kinase (PI3K)/serine threonine protein kinase Akt signaling.…”
Section: Prl1mentioning
confidence: 99%